Hubungan Pengetahuan Dengan Sikap Remaja Tentang Seks Pranikah Di SMK Widya 1 Batam Tahun 2020 - Fadhilatul Huryah (Sekolah Tinggi Ilmu Kesehatan Yatsi, 2021)
Introduction: Adolescence is a transition period from childhood to adulthood which begins when the child shows signs of puberty and is followed by changes from non-sexual to sexual in individuals. A comfortable environment and place are supporting factors for having free sex or premarital sex, unhealthy sexual behavior among adolescents, especially unmarried adolescents, tends to increase. Problem: The purpose of this study was to determine the relationship between knowledge and adolescent attitudes about premarital sex at SMK Widya 1 Batam in 2020. Design: The design of this study was quantitative descriptive by giving questionnaires to respondents. The population in this study were all students at SMK Widya 1 Batam, totaling 37 students. The sampling technique was taken by Total Sampling as many as 37 students. Analysis: Based on data analysis conducted regarding the frequency distribution of knowledge about premarital sex at SMK Widya 1 Batam, 19 respondents (51%) had good knowledge, 13 respondents (35%) had sufficient knowledge and 5 respondents (14%) had less knowledge. Frequency distribution of adolescent attitudes about premarital sex at SMK Widya 1 Batam 15 respondents (41%) have a good attitude, 16 respondents (43%) are moderate and 6 respondents (16%) are lacking. Bivariate analysis using chi square test and data collected using a questionnaire sheet. The results of this study obtained a bivariate P value of 0.04 < 0.05, meaning that it indicates that there is a relationship between knowledge and attitudes about premarital sex. Discussion: To overcome the problem of knowledge and attitudes of adolescents at SMK Widya 1 Batam, it is necessary to include it in learning ways about premarital sex. to students. Keywords: Knowledge, Attitudes, Premarital Sex